Neuroprotective effects on microglia and insights into the structure–activity relationship of an antioxidant peptide isolated from Pelophylax perezi - Plácido, Alexandra; Amaral, Constança do Pais do; Teixeira, Cátia; Nogueira, Ariane; Brango-Vanegas, José; Barbosa, Eder Alves; Moreira, Daniel C.; Carvalho, Amandda É. Silva; Silva, Maria da Gloria da; Dias, Jhones do Nascimento; Albuquerque, Patrícia; Saldanha-Araújo, Felipe; et al. (Wiley, 2022)
Tryptophyllins constitute a heterogeneous group of peptides that are one of the first classes of peptides identified from amphibian’s skin secretions. Here, we report the structural characterization and antioxidant properties of a novel tryptophyllin-like peptide, named PpT-2, isolated from the Iberian green frog Pelophylax perezi. The skin secretion of P. perezi was obtained by electrical stimulation and fractionated using RP-HPLC. De novo peptide sequencing was conducted using MALDI MS/MS. The primary structure of PpT-2 (FPWLLS-NH2) was confirmed by Edman degradation and subsequently investigated using in silico tools. PpT-2 shared physicochemical properties with other well-known antioxidants. To test PpT-2 for antioxidant activity in vitro, the peptide was synthesized by solid phase and assessed in the chemical-based ABTS and DPPH scavenging assays. Then, a flow cytometry experiment was conducted to assess PpT-2 antioxidant activity in oxidatively challenged murine microglial cells. As predicted by the in silico analyses, PpT-2 scavenged free radicals in vitro and suppressed the generation of reactive species in PMA-stimulated BV-2 microglia cells. We further explored possible bioactivities of PpT-2 against prostate cancer cells and bacteria, against which the peptide exerted a moderate antiproliferative effect and negligible antimicrobial activity. The biocompatibility of PpT-2 was evaluated in cytotoxicity assays and in vivo toxicity with Galleria mellonella. No toxicity was detected in cells treated with up to 512 µg/ml and in G. mellonella treated with up to 40 mg/kg PpT-2. This novel peptide, PpT-2, stands as a promising peptide with potential therapeutic and biotechnological applications, mainly for the treatment/prevention of neurodegenerative disorders.
Keywords: Amphibia; antioxidant; bioactive peptide; neuroprotection; Pelophylax perezi; tryptophyllin